Social Determinants of Health: What's a Healthcare System to Do?. Issue 4 (July 2019) - Gottlieb, Laura; Fichtenberg, Caroline; Alderwick, Hugh; Adler, Nancy
Abstract : EXECUTIVE SUMMARY: A growing literature regarding the health consequences of social risks, such as substandard housing and food insecurity, combined with increased adoption of risk-based payment models have contributed to a wave of healthcare sector initiatives focused on the social determinants of health. Yet decisions about how and when to address adverse social conditions are frequently guided by limited information about potential interventions and a lack of data on their effectiveness. We describe four complementary strategies that healthcare leaders can pursue to intervene on social adversity, split between patient care and community-level approaches. Patient care strategies rely on data about patients' social risks to adapt medical care or improve patients' social circumstances directly. Community-level strategies focus on improving the broader health and well-being of the local population through a mix of direct investments in communities and collaboration through multisector partnerships. Each approach presents unique incentives and challenges, and healthcare systems wanting to address social adversity may adopt one or more. Understanding the range of potential choices may help healthcare leaders make more informed choices in response to patient needs and changing payment and policy initiatives.